Pengaruh Kompetensi Sumber Daya Manusia Terhadap Kinerja Karyawan Melalui Kompensasi Sebagai Variabel Mediasi: Studi Pada Karyawan Bank Pembiayaan Rakyat Syariah (BPRS) Bhakti Sumekar Sumenep - Imam Baihaki; Rusdiayanto Rusdiayanto; Mei Indrawati (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
Imam Baihaki, 2025. The Effect of Human Resources Competencies on Employee Performance through Compensation as a Mediating Variable (Study on Employees of Sharia People's Financing Bank (BPRS) Bhakti Sumekar Sumenep), Postgraduate Program, Wijaya Putra University. This type of research is explanatory this research intends to provide an explanation of the causal relationship between the independent variable and the dependent variable through hypothesis testing, using a quantitative approach, the research sample was 76 respondents. In this study the data will be processed using SEM-PLS data analysis.The objectives of this study are: 1) To test and analyze the direct effect of human resource competencies on compensation. 2) To test and analyze the direct effect of human resource competencies on performance. 3) To test and analyze the direct effect of compensation on employee performance. 4) To test and analyze the indirect effect of human resource competencies on employee performance. The results showed that: 1) human resource competencies have a direct and significant effect on compensation. 2) human resource competencies have a direct and significant effect on employee performance. 3) compensation has a direct and significant effect on employee performance. 4) human resource competencies have an indirect and significant effect on employee performance mediated by compensation.